RANCANG BANGUN SISTEM COMPUTER BASED TEST (CBT) BERBASIS WEBSITE PADA MIS GUPPI SAWANG LEBAR (UNIB Press, 2024)
Currently, MIS Guppi Sawang Lebar has a Computer Laboratory but the facility cannot be utilized properly and MIS Guppi Sawang Lebar wants to hold exams that utilize computers to simulate exams conducted through computers held by the government. However, MIS Guppi Sawang Lebar has several limitations, such as the absence of supporting software to conduct exams via computer. So a Computer Based Test (CBT) System will be designed and built at MIS Guppi Sawang Lebar. The research method applied is the development of web-based information systems. This development uses various technologies, including HTML, PHP, Bootstrap, and Laravel as a framework, as well as MySQL as database management. The result of the development of this Computer Based Test (CBT) System is that users have access to complete features. The admin page allows to add users, create exam lists, assign sessions, and view score graphs. On the other hand, the user page allows to view the exam session schedule and information about the exam to be conducted. With the existence of the system, it is expected to make it easier for MIS Guppi Sawang Lebar in the exam process that uses computers.